Penerapan Model Team Assisted Individualization (TAI) Dengan Pendekatan Reciprocal Teaching Pada Pembelajaran Matematika - Salahuddin, Muhammad; Atmaja, Jessy Parwati (STKI Harapan Bima, 2023)
This research has the objectives to:(1)know the application of Team Assisted Individualization Model with Reciprocal Teaching approach at learning Mathematics 8th Grade on the State Junior High School 13 Malang. (2) Determine students' learning activities on learning mathematics by using the Team Assisted Individualization Model with Reciprocal Teaching approach (3)Determine students learning outcomes in mathematics learning using Team Assisted Individualization Model with Reciprocal Teaching approach.The approaches used in this study are qualitative and descriptive qualitative approach. This research was conducted at State Junior High School 13 Malang on July 22, 2013 until August 20, 2013. The Subjects in this study is Team Assisted Individualization model (TAI) with Reciprocal Teaching approach, whereas the objects of this study are the eighth grade students of Junior high school 13 state of Malang. The instruments used in this study were the form of teacher and students observation sheet activities. Whereas, the learning outcomes while students individually or classical is by providing questions test to the students in the form of description while the implementation of learning Team Assisted Individualization Model with Reciprocal Teaching Approach. Begins with a brief description of the teacher followed by break out the groups where each groupshave to learn the material that has been given then split them from each member of the groups in charge of any such role summarizer,questioner,clarifier, and predicor. After the group has split, students have to discuss to resolve a given problems on a given sheet of material.The results showed that: (1) the application of the method of Team Assisted Individualization with Reciprocal Teaching approach in the learning of mathematics has been performing well in accordance with the sintak that has been planned. (2) Students’ activities in the context area of learning math by using Team Assisted Individualization model (TAI) with Reciprocal Teaching as approach have category well. However, there are indicators on the oral activity of expression activities that students are still less well done that is equal to 49.79 % and (3) the learning outcomes of students in learning mathematics using Team Assisted Individualization (TAI) with Reciprocal Teaching approach demonstrate mastery level of 77.5 % with average gained 75.25 for students.